ANALYSIS OF MATERIALS TECHNOLOGY DEVELOPMENT IN SUPPORTING SUSTAINABLE DEVELOPMENT IN THE FIELD OF CIVIL ENGINEERING - Dwi Ari Suryaningrum (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
In supporting sustainable development in the field of civil engineering, the development of materials technology plays an important role. Sustainable materials technology can help create environmentally friendly, efficient and long-lasting construction. The development of materials technology in the field of civil engineering is an important step in supporting sustainable development. By focusing on the use of environmentally friendly materials, efficient use of materials, structural sustainability, and innovation in construction technology, civil engineering can contribute to creating sustainable and environmentally friendly infrastructure. The development of materials technology in civil engineering contributes significantly to sustainable development goals. By prioritizing environmentally friendly, energy efficient, durable and innovative materials, the construction industry can build infrastructure that not only meets today's needs, but is also sustainable for the future. Apart from that, this approach also supports the social and economic welfare of society, making it a main pillar in sustainable development.